Kewenangan Penyidik Pasca Putusan Praperadilan - Fona Azhara Sandi; Fathur Rachman; Ino Susanti (VIVA THEMIS, 2018)
One form of protection of human rights can be seen by the rules governing pretrial as stipulated in Article 77 to Article 83 of the Criminal Procedure Code.The problem in this study is how is the investigator's authority after the pretrial verdict in the Tanjung Karang Class I District Court? and what are the inhibiting factors of the investigator's authority after the pretrial verdict in the Tanjung Karang Class I District Court?This study uses a normative approach and empirical approach with secondary data obtained through literature studies and primary data obtained through field studies with interviews. The data is then analyzed qualitatively.The results of the study show that the investigator's authority after the pretrial verdict in the Tanjung Karang Class I District Court must be based on the provisions contained in the Criminal Procedure Code, specifically Article 77 of the Criminal Procedure Code which regulates the pretrial object. The inhibiting factor of the investigator's authority after the pretrial verdict in the Tanjung Karang District Court is the determination of the suspect's status as part of the investigation and Article 82 Paragraph (3) of the Criminal Procedure Code that in the event that an arrest or detention is illegal. This decision is of course a jurisprudence that can be used by other judges as a reference in making decisions in pretrial institutions. Investigators are advised to carry out investigations based on applicable provisions of criminal procedural law in order to anticipate pretrial requests, so that actions taken by investigators can run effectively and efficiently in the context of law enforcement. Pre-trial Judges are advised to maintain objectivity in deciding pretrial applications.